Interactive Effects of AB Mix Nutrient and Gandasil D Fertilizer on Productivity of Pakcoy (Brassica rapa L.) in Wick Hydroponics - Chintia Dinda Mellyaningtyas; Ramdan Hidayat; Yonny Koentjoro (Universitas Labuhanbatu, 2025)
Background: National Pakcoy (Brassica rapa L.) production declined by approximately 9.69 % from 2022 to 2023 due to climate variability, suboptimal cultivation practices, and agricultural land-use conversion, highlighting the need for alternative production strategies. Wick-based hydroponic cultivation with optimized nutrient management using AB Mix and Gandasil D foliar fertilizer is therefore investigated for its potential to enhance nutrient uptake efficiency, vegetative growth, and yield of pakcoy in a sustainable manner. Methodology: the study conducted in Gubeng District, Surabaya, utilized a factorial Completely Randomized Design (CRD). The first factor was AB Mix concentration (500 ppm, 1000 ppm, 1500 ppm), and the second was Gandasil D foliar fertilizer concentration (Control, 1 g/L, 2 g/L, 3 g/L). Observation parameters include, plant length (cm), leaf area (cm2), total fresh weight, shoot fresh weight, and shoot dry weight. Further analysis was performed using the Honestly Significant Difference (HSD) test at a 5% significance level. Findings: showed a significant interaction between the AB Mix concentration and Gandasil D foliar fertilizer on the plant shoot dry weight, with the highest yield (6.27 g) achieved by the combination of 1500 ppm AB Mix and 2 g/L Gandasil D. The single treatment of 1500 ppm AB Mix concentration yielded the best average for all observed parameters, including: plant length (16.73 cm), leaf area (688.04 cm2), total fresh weight (64.15 g), shoot fresh weight (51.56 g), and shoot dry weight (6.27 g). The 2 g/L Gandasil D concentration treatment provided the highest results for total fresh weight (56.09 g) and shoot fresh weight (45.28 g). The combination of 1,500 ppm AB Mix and 2 g/L Gandasil D demonstrated the most optimal results for the growth and yield of pakcoy plants compared to other treatment combinations. Contribution: These findings provide information regarding the selection of the optimal AB Mix and Gandasil D concentrations to maximize the growth and yield of pakcoy in the wick hydroponic system, which can be utilized in educational or training programs for communities practicing urban farming